Abstract splines in Krein spaces - Giribet, Juan Ignacio (2010)
We present generalizations to Krein spaces of the abstract interpolation and smoothing problems proposed by Atteia in Hilbert spaces: given a Krein space K and Hilbert spaces H and E (bounded) surjective operators T:H→K and VH→E, ρ>0 and a fixed z0∈E, we study the existence of solutions of the problems argmin{[Tx,Tx]K: Vx=z0} and argmin{[Tx,Tx]K+ρnorm of matrixVx-z0norm of matrixE2x∈H}.